Subjective and Objective Cognitive Dysfunction in Schizophrenia – is there a Link? - Homayoun, Saffron; Stip, Emmanuel; Luck, David; Nadeau-Marcott, Frédérique (Frontiers in Psychology, 2011)
Cognitive dysfunction is a well recognized symptom of schizophrenia, as well as patients having poor insight into their illness. The Subjective Scale to Investigate Cognition in Schizophrenia (SSTICS) is one of several scales that have been developed to study subjective cognitive dysfunction and has been compared to patients’ objective cognitive level. A literature search was performed using Pubmed, PSYCHinfo, Web of Science and cross-referencing to find 26 articles which used 14 different subjective cognitive dysfunction scales to investigate the relationship between subjective and objective measures of cognition in schizophrenia. Although the majority of studies using the SSTICS found significant correlations between subjective and objective measures of cognition, the findings from the other scales were less clear. From this review, the issue of whether or not schizophrenic patients have good cognitive insight remains unsure. However, due to the heterogeneous nature of the study designs and their outcome measures, continued work in this area with consistency on these points is necessary; on the path to better provide management options for a very debilitating component of this illness.